2005
DOI: 10.1002/art.21523
|View full text |Cite
|
Sign up to set email alerts
|

Activation of receptor for advanced glycation end products in osteoarthritis leads to increased stimulation of chondrocytes and synoviocytes

Abstract: Objective. The major risk factor for osteoarthritis (OA) is aging, but the mechanisms underlying this risk are only partly understood. Age-related accumulation of advanced glycation end products (AGEs) could be one of these mechanisms. We undertook this study to investigate the role of the receptor for AGEs (RAGE) in mediating the cellular effects of AGEs on chondrocytes and fibroblast-like synoviocytes (FLS).Methods. AGE levels in human cartilage were determined by fluorescence, browning, and pentosidine leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 53 publications
4
112
1
Order By: Relevance
“…It has been well established that RAGE serves as an amplification factor in various inflammatory cellular dysfunctions and is associated with the development of diabetic vascular complications, neurodegenerative disorders, rheumatoid arthritis, and other inflammatory diseases (23,(51)(52)(53)(54). As a member of the Ig superfamily proteins, RAGE is capable of binding to multiple ligands thus mediating diverse functions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that RAGE serves as an amplification factor in various inflammatory cellular dysfunctions and is associated with the development of diabetic vascular complications, neurodegenerative disorders, rheumatoid arthritis, and other inflammatory diseases (23,(51)(52)(53)(54). As a member of the Ig superfamily proteins, RAGE is capable of binding to multiple ligands thus mediating diverse functions.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with normal healthy cartilage, OA cartilage contains obvious accumulations of AGEs and shows upregulation of RAGE [27]. Studies have shown that inflammation-induced cartilage hypertrophy is induced by AGEs in OA.…”
Section: Discussionmentioning
confidence: 99%
“…44 Activation of these receptors by cartilage damage as well as by proinflammatory cytokines contributes to the complex detrimental cascade of cartilage damage. As the disease progresses, these different cascades and events appear to function as positive feedback mechanisms with an avalanche-like effect on the destruction of the joints, the associated loss of function and with an increase in pain.…”
Section: Loss Of the Chondrocyte ' S Stable Phenotype -A Role For Dammentioning
confidence: 99%